1993
DOI: 10.1002/gepi.1370100504
|View full text |Cite
|
Sign up to set email alerts
|

Epistatic modeling in rheumatoid arthritis: An application of the Risch theory

Abstract: Rheumatoid arthritis (RA) is a disease of unknown etiology but with a presumed complex pattern of inheritance. Risch [Am J Hum Genet 46:222-228, 1990] has shown that the recurrence risk ratio, lambda R, (which is defined as the risk to type R relatives vs. the population prevalence) can be used to evaluate patterns of inheritance in genetically complex diseases. We have used the Risch theory to examine some multiple locus models of inheritance in RA. Recurrence risk ratios in MZ twins and in 1st, 2nd, and 3rd … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 30 publications
(16 reference statements)
0
24
0
Order By: Relevance
“…The heritability, estimated from twin studies, is 40-60% (2,3). Recurrence risk modeling suggests that the genetic susceptibility is encoded by a limited number of genes with significant genetic epistasis (4)(5)(6).…”
mentioning
confidence: 99%
“…The heritability, estimated from twin studies, is 40-60% (2,3). Recurrence risk modeling suggests that the genetic susceptibility is encoded by a limited number of genes with significant genetic epistasis (4)(5)(6).…”
mentioning
confidence: 99%
“…Modeling studies suggest that the genetic susceptibility is encoded by a limited number of genes, with significant genetic epistasis, and there is evidence for more than one susceptibility gene within the MHC (6)(7)(8). The MHC is an extremely gene-dense region with Ͼ300 genes, of which ϳ50% are thought to have immunoregulatory functions (9).…”
mentioning
confidence: 99%
“…Under the recessive model, the prevalence is 1.3% and the recurrence risk to female siblings is 4.3%. These recurrence risks fall within the range of risks provided in the summary manuscript of Rigby et al 14 We used the package Analyze 46 to perform linkage analyses and homogeneity tests. 47 …”
Section: Linkage Analysismentioning
confidence: 99%
“…Estimation of the genetic contribution of HLA suggests that less than 40% of RA susceptibility can be attributed to MHC-linked genes. 14,15 Multiple studies have reported a possible association or linkage with a variety of non-MHC genes and loci, most notably the T cell receptor B chain. Positive population associations with TCRB alleles have been reported by some groups, 16,17 but not others.…”
Section: Introductionmentioning
confidence: 99%